2018
DOI: 10.12691/jcrt-6-1-3
|View full text |Cite
|
Sign up to set email alerts
|

3-bromopyruvate as a Promising Treatment for Hematological Cancer

Abstract: Many biological differences exist between cancer cells and normal cells that can act as potential targets in targeted cancer therapy. Hematological cancers e.g. lymphoma, leukemia and myeloma exhibit drug-resistance that ultimately results in deteriorated patients' conditions and high mortality rates. Resistance of hematological malignancy to conventional chemotherapy is attributed in part to upregulation of glucose oxidation (glycolysis) genes evidenced by gaining a promising chemosensitization effect upon ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…The ROS generation in K-562 cells was four-fold high as compared with THP-1 cells suggestive of K-562 is an aggressive Warburg phenotype [43]. We hypothesized that inhibition of glycolysis and HK-II mitochondrial association using 3-BP, a pyruvate analog and a potent inhibitor of HK-II can weaken the aggressiveness of Warburg phenotype K-562 cells and make it susceptible to anthracycline anticancer agent, DNR [23,44]. We found that 3-BP synergistically sensitized and increased the susceptibility of K-562 cells to 10 nM DNR, by two-fold (29–58% and SI ≥ 1, Figure 2C).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The ROS generation in K-562 cells was four-fold high as compared with THP-1 cells suggestive of K-562 is an aggressive Warburg phenotype [43]. We hypothesized that inhibition of glycolysis and HK-II mitochondrial association using 3-BP, a pyruvate analog and a potent inhibitor of HK-II can weaken the aggressiveness of Warburg phenotype K-562 cells and make it susceptible to anthracycline anticancer agent, DNR [23,44]. We found that 3-BP synergistically sensitized and increased the susceptibility of K-562 cells to 10 nM DNR, by two-fold (29–58% and SI ≥ 1, Figure 2C).…”
Section: Discussionmentioning
confidence: 99%
“…However, data presented here suggest that the combined DNR and 3-BP treatment leads to profound accumulation of cells in both S phase and G 2 /M phase resulting in significantly higher growth delay. It has been found that mitochondrial dissociation of HK-II is the consequence of 3-BP induced covalent modification followed by the commencement of apoptosis in cancer cells [23,44]. Therefore we examined the correlation between 3-BP induced HK-II dissociation from mitochondria and apoptosis in K-562 cells.…”
Section: Discussionmentioning
confidence: 99%